THU0198 Risk of Hospitalized Serious Infection in Spondylitis Ankylosing (AS) Patients Using Nbdmard or Anti-TNF. (9th June 2015) - Moura, C.S.; Rahme, E.; Maksymowych, W.P.; Abrahamowicz, M.; Bessette, L.; Bernatsky, S.
Abstract : Background: Nonbiologic Disease-modifying anti-rheumatic drugs (nbDMARDs) and anti-tumor necrosis factor (anti-TNFs) have been used in AS patients who do not respond adequately to non-steroidal anti-inflammatories (NSAIDs). However, concerns exist regarding the risk of serious infections 1 . Objectives: To assess the risk of serious infections associated with nbDMARDs or anti-TNF use in an AS cohort. Methods: We assembled a cohort of potential AS patients identified from hospitalization discharge diagnoses or physician visit billing claims, using ICD-9 code 720 or ICD10 code M45. Patients were required to have two or more ICD codes and at least one anti-TNF or nbDMARD exposure between January 1, 2001 and December 31, 2011. Cohort entry was defined as the date of the first of these prescriptions and analysis was restricted to individuals who had not used anti-TNF drugs prior to cohort entry. Patients were excluded if they were not covered by the Quebec drug plan 1 year before the first prescription of nbDMARDs and/or an anti-TNF agent. We used Cox regression with the following three time-varying drug exposure categories: 1) nbDMARDs, 2) anti-TNF agents alone or in combination with nbDMARDs, and 3) neither drug. Models were adjusted for baseline patient sociodemographics, co-morbidity, prior health service use, and time-dependent use of NSAIDs, and corticosteroids. Current time-dependent corticosteroids dose was standardized according to the Defined Daily Dose (DDD) system. The outcome, first occurrence of an infection requiring hospitalization, was identified from hospitalization discharge diagnoses (primary or non-primary). Results: We studied 714 AS patients; 469 (65.7%) were men, with a mean age of 50.3 (standard deviation 14.1) years at cohort entry. During this period, 57 cases of serious infections occurred, for an incidence rate of 3.07/100 PY. The median time from cohort entry to serious infection was 2.1 years. The incidence of serious infection was 4.12/100 PY in patients exposed to nbDMARDs alone, 2.44/100 PY in the anti-TNF +/- nbDMARDs group, and 2.25/100 PY in unexposed patients. Age, prior health service use, and use of corticosteroids in the previous year were associated with increased risk of infection in our multivariate analysis. The 95% confidence intervals, CIs, for the adjusted hazard ratios (HR) of infection (with the unexposed group as comparator) were wide and overlapping for both anti-TNF+/- nbDMARDs (HR=1.05; 95% CI 0.45-2.45) and nbDMARDs alone (HR=1.77; 95% CI 0.78-4.02). Conclusions: We present novel findings demonstrating that the risk of serious infection in AS is 3% per year. In the current analyses, we were unable to draw definitive conclusions regarding the whether serious infections in AS are higher with anti-TNF or nbDMARDs use, versus non-use. However, older age, prior health service use, and use of corticosteroids appear to be important risk factors for serious infection in AS. References: Grijalva CG et al. (2011). Initiation of tumor necrosis factor-α antagonists and the risk of hospitalization for infection in patients with autoimmune diseases. JAMA. 306(21):2331-9. Acknowledgements: Canadian Institutes for Health Research (CIHR) Disclosure of Interest: None declared